2019
DOI: 10.1136/annrheumdis-2018-214326
|View full text |Cite
|
Sign up to set email alerts
|

Risk of serious infections in patients with rheumatoid arthritis treated in routine care with abatacept, rituximab and tocilizumab in Denmark and Sweden

Abstract: ObjectiveTo estimate (1) crude and age-and gender-adjusted incidence rates (IRs) of serious infections (SI) and (2) relative risks (RR) of SI in patients with rheumatoid arthritis (RA) initiating treatment with abatacept, rituximab or tocilizumab in routine care.MethodsThis is an observational cohort study conducted in parallel in Denmark and Sweden including patients with RA in Denmark (DANBIO) and Sweden (Anti-Rheumatic Treatment in Sweden Register/Swedish Rheumatology Quality Register) who started abatacept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 31 publications
3
45
0
1
Order By: Relevance
“…Of the 42 observational studies, 16 addressed the risk of infections in patients receiving bDMARDs (3 also included patients on tofacitinib),10–25 8 studies focused on malignancies,16 26–32 with all except one (comparing MTX to the general population),27 assessing patients on bDMARDs. The risk of MACEs was evaluated in 10 studies, all performed in patients treated with bDMARDs,16 33–41 with one also including patients on tofacitinib 33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 42 observational studies, 16 addressed the risk of infections in patients receiving bDMARDs (3 also included patients on tofacitinib),10–25 8 studies focused on malignancies,16 26–32 with all except one (comparing MTX to the general population),27 assessing patients on bDMARDs. The risk of MACEs was evaluated in 10 studies, all performed in patients treated with bDMARDs,16 33–41 with one also including patients on tofacitinib 33.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 16 studies addressing the risk of infections, 3 compared bDMARDs with csDMARDs,10 21 25 and 13 compared the risk across bDMARDs (table 1 and online supplementary tables S2–S31). 11–20 22–24 Three of these studies also compared tofacitinib with bDMARDs 14 17 18…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have described the effect of rituximab on the B cell cytokine network, mainly on B effector and B regulator cells, with a secondary influence on T helper cell response [21,22]. Some studies have reported a higher risk of infection in RA patients treated with rituximab than those treated with other biologic DMARDs [23,24] but these data come from registries and retrospective studies, which may contain bias due to their observational designs. The effects of rituximab on the immune system response to SARS-CoV-2 infection have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the insights from these postmarketing studies, a number of real-world and registry-based studies provide additional insight into the safety profile of these agents in the wider population of patients with RA. While data from some registries have suggested an increased risk of infections, including serious infections, with agents that inhibit IL-6 signaling [244][245][246][247], a comparative head-to-head analysis of the safety of tocilizumab and TNF inhibitors in the Japanese REAL registry did not find a higher risk for serious adverse events or serious infections with tocilizumab compared with TNF inhibitors after adjustment for potentially confounding factors. The use of oral corticosteroids in patients receiving tocilizumab, however, was a significant risk factor for both serious adverse events and serious infections [248].…”
Section: Safety and Tolerability Of Il-6 Blockadementioning
confidence: 88%